2023
DOI: 10.7554/elife.81127
|View full text |Cite
|
Sign up to set email alerts
|

International multicenter study comparing COVID-19 in patients with cancer to patients without cancer: Impact of risk factors and treatment modalities on survivorship

Abstract: Background: In this international multicenter study we aimed to determine the independent risk factors associated with increased 30-day mortality and the impact of cancer and novel treatment modalities in a large group of patients with and without cancer with COVID-19 from multiple countries.Methods: We retrospectively collected de-identified data on a cohort of patients with and without cancer diagnosed with COVID-19 between January and November 2020, from 16 international centers.Results: We analyzed 3966 CO… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In an international multicenter study of 3,966 COVID-19 patients, primarily designed to evaluate 30-day mortality in patients with (n=1,115) or without cancer (n=2,851), RDV was the only therapeutic agent that independently decreased 30-day all-cause mortality in the entire population (p=0.036), including the oncological patients [OR=0.44 (95%CI=0.20-0.96; p=0.04)]. Of note, in line with ACTT-1 findings, RDV benefit was more pronounced in patients with pneumonia and mild hypoxia who were receiving low-flow oxygen (≤6 l/min) (26,29). Lastly, the contributing factors to increased mortality in cancer patients were sought in the real-world CSOVID-19 study and 222 haemato-oncological patients (HM: n=60, other type of malignancy: n=162) with active disease were analyzed.…”
Section: Discussionmentioning
confidence: 73%
“…In an international multicenter study of 3,966 COVID-19 patients, primarily designed to evaluate 30-day mortality in patients with (n=1,115) or without cancer (n=2,851), RDV was the only therapeutic agent that independently decreased 30-day all-cause mortality in the entire population (p=0.036), including the oncological patients [OR=0.44 (95%CI=0.20-0.96; p=0.04)]. Of note, in line with ACTT-1 findings, RDV benefit was more pronounced in patients with pneumonia and mild hypoxia who were receiving low-flow oxygen (≤6 l/min) (26,29). Lastly, the contributing factors to increased mortality in cancer patients were sought in the real-world CSOVID-19 study and 222 haemato-oncological patients (HM: n=60, other type of malignancy: n=162) with active disease were analyzed.…”
Section: Discussionmentioning
confidence: 73%
“…Chronic kidney disease, the incidence of acute kidney injury, and atrial fibrillation have been shown to be comorbidities associated with reduced survival in patients hospitalized for COVID-19 [73]. Other studies confirm that lymphopenia, often observed in cancer patients, is associated with a higher risk of mortality [74]. Hematological disorders are also seen as additional health conditions that can negatively impact the effectiveness of antiviral treatments such as remdesivir [75].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic kidney disease, the incidence of acute kidney injury, and atrial fibrillation have been shown to be comorbidities associated with reduced survival in patients hospitalized for COVID-19 [77]. Other studies confirm that lymphopenia, often observed in cancer patients, is associated with a higher risk of mortality [78]. Hematological disorders are also seen as additional health conditions that can negatively impact the effectiveness of antiviral treatments such as remdesivir [79].…”
Section: Discussionmentioning
confidence: 99%